2021
DOI: 10.1111/infa.12393
|View full text |Cite
|
Sign up to set email alerts
|

Social interaction targets enhance 13‐month‐old infants' associative learning

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 50 publications
(68 reference statements)
1
12
0
Order By: Relevance
“…Infants' looking preference disappears when seeing the same stimuli upside down, indicating that the longer looking times at upright face-to-face scenes do not reflect a response to the low-level perceptual features, but rather a greater interest compared to the "competing" back-to-back scene (Galazka et al, 2014). This interpretation is further supported by a previous study showing that 13-month-old infants organize their attention and associative learning in favor of predicting and actively approaching situations in which they can observe a face-to-face interaction (Thiele, Hepach, Michel, Gredebäck, & Haun, 2021).…”
supporting
confidence: 57%
See 1 more Smart Citation
“…Infants' looking preference disappears when seeing the same stimuli upside down, indicating that the longer looking times at upright face-to-face scenes do not reflect a response to the low-level perceptual features, but rather a greater interest compared to the "competing" back-to-back scene (Galazka et al, 2014). This interpretation is further supported by a previous study showing that 13-month-old infants organize their attention and associative learning in favor of predicting and actively approaching situations in which they can observe a face-to-face interaction (Thiele, Hepach, Michel, Gredebäck, & Haun, 2021).…”
supporting
confidence: 57%
“…Previous studies have shown that infants find it intrinsically rewarding to engage in social interactions, and that this social motivation increases during the second half of the first year of life (Striano & Bertin, 2005;Venezia, Messinger, Thorp, & Mundy, 2004). Considering the possibility that infants find it also intrinsically valuable to observe others' interactions (e.g., Thiele et al, 2021), it would be possible that social reward-seeking mechanisms underlie the parallel increase in infants' attention to direct interaction partners and others' interactions. Another factor that may influence infants' behavior at the broader level is a more general motivation to establish and foster social bonds with social group members (Over, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, infants' attention to social contingency increases with age and becomes dissociated from morphological properties of interlocutors, which may be the reason why we begin to observe its effects on the development of verbal reference by 12-14 months and not earlier. For example (as reviewed in Thiele et al, 2021), at 6 months, infants shift visual attention to a reciprocal social interaction of two people facing each other (Augusti, 2010). By 12 months, infants look longer at socially contingent over nonsocially contingent events (Bakker et al, 2011) and engage in gaze following (or orientation) with entities that act in a socially contingent way, even if they do not have faces (Johnson et al, 1998).…”
Section: Observed Mother-infant Dyads When Infantsmentioning
confidence: 99%
“…On the other hand, if one patron, standing second in line, observes the patron in front of them order an unusual drink and then decides to order it for the first time themselves, without ever speaking to the other patron, this is better interpreted as the imitator attempting to learn about a new potential reward from the model. Infants are capable of using cues such as proximity, orientation, and contingency to recognize social interaction (Beier & Spelke, 2012;Fawcett & Gredeback, 2013;Powell & Spelke, 2013;Papeo, et al, 2020;Thiele et al, 2021), and it is plausible that these cues impact the inferences and evaluations they make from observations of imitation. The influence of interaction context on social inference may also explain how parallel play functions as an affiliative activity for toddlers (Parten, 1933;Rubin, et al, 1978;Bakeman & Brownlee, 1980): so long as their social cues establish that they are engaged in a joint interaction, children's play need not depend on one another's actions for success in order to encompass a shared goal.…”
Section: Disambiguating Affiliation From Other Motives For Imitationmentioning
confidence: 99%